Biofarmasetics and Pharmacokinetics Study Analysis of Paracetamol Excretion Through Urine and Saliva - Nahla Akila Fikria (Pt. Anagata Sembagi Education, 2024)
The purpose of this study was to determine that Paracetamol, also known as acetaminophen, is a commonly used analgesic and antipyretic drug to relieve pain and reduce fever. The process of metabolism and elimination of paracetamol from the body is important to understand, especially in the context of the safe use of this drug. This study aims to analyze the biopharmaceutics and pharmacokinetics studies of paracetamol excretion through urine and saliva as important indicators in understanding the metabolic and elimination processes of this drug. Paracetamol is rapidly and efficiently absorbed through the gastrointestinal tract, reaches the highest concentration in plasma in a short time, and is dispersed throughout the body fluids. The metabolic process of paracetamol mainly occurs in the liver, through two main phases: oxidation and conjugation with glucuronic and sulfuric acids. Excretion of drugs and their metabolites can occur through urine and saliva, with the kidney as the main organ in the excretion process. Qualitative analytical methods were used in this study to identify paracetamol metabolite compounds in urine and saliva samples and to evaluate the metabolic pathways involved. Glucoronide, sulfate, and phenol conjugate assays were used to detect the presence of paracetamol metabolites in the samples. The assay results showed that urine was more effective in excreting paracetamol compared to saliva. In conclusion, this study provides a better understanding of the metabolic process and elimination of paracetamol from the human body through the analysis of biopharmaceutics and pharmacokinetics studies. These results are important for understanding the therapeutic effects and toxicity of paracetamol as well as for developing more effective and safe drug use management strategies.